Hatching Rate of Koi Fish (Cyprinus Carpio) Eggs on Different Types of Substrates - Linda Aini Putri; Nunik Cokrowati; Dewi Putri Lestari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The Cyprinus carpio koi fish is a freshwater ornamental fish that is excellent because it has a beautiful and bright colour. This study aimed to determine the best substrate for the attachment of C. carpio koi fish eggs and the success rate of hatching koi fish eggs. The method used in this study is the experimental method with description analysis. The treatments in this study were 4 types of substrates, P1 (raffia), P2 (brush), P3 (ijuk), and P4 (Hydrilla). The results obtained that the highest fungal exposure was found in P3 with a value of 358 grains, the highest hatchability was found in P4 at 94% and P1 at 93%. The highest survival rate in koi fish was found in the P4 treatment with a value of 92%. This study concluded that the substrate with the highest egg attachment was found in P4 (Hydrilla) and the success rate of hatching eggs was found in P1 (raffia) and P4 (Hydrilla) because both had no significant effect.